Searching with Friends - Stefano Caria; Simon Franklin; Marc Witte (Institute of Labor Economics (IZA), 2020)
We study how active labor market policies affect the exchange of information and support among jobseekers. Leveraging a unique social network survey in Ethiopia, we find that a randomized job-search assistance intervention reduces information sharing and support between treated jobseekers and their active job-search partners. Due to lower job-search support, untreated individuals search less and, suggestively, have worse employment outcomes. These results are explained by a model of networks where unemployed individuals form job-search partnerships to exploit the complementarities of job search. These partnerships are broken if policy creates inequality in the access to information about job vacancies.
Keywords: D85; L14; O12; J64; D8; 330; job search; social networks; RCT; active labor market policies